2017
DOI: 10.1007/s11252-017-0667-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of alien and native plant species in Trieste port area: exploring the role of urban habitats in biodiversity conservation

Abstract: Nowadays, urban areas play a crucial role in biodiversity conservation and habitat protection despite the constant pressures on which these habitats are subjected. They may even host relatively new plant communities due to the peculiar ecosystem where they vegetate. The port of Trieste (NE Italy) is characterized by a mixed mosaic of intensely human impacted areas (where commercial activities are still ongoing) flanked by abandoned areas where vegetation persists or has spontaneously recovered. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…This indicates that alien species tend to share species composition increasing the scale of analyses. A similar pattern has also been described in Tordoni et al (2017) for a coastal urban context. Although the richness values of native and alien species were correlated at the plot scale, it has been clearly demonstrated that most likely it is the beta diversity of both species groups which regulate equilibrium in the plant community.…”
Section: Beta Diversity Patternssupporting
confidence: 84%
“…This indicates that alien species tend to share species composition increasing the scale of analyses. A similar pattern has also been described in Tordoni et al (2017) for a coastal urban context. Although the richness values of native and alien species were correlated at the plot scale, it has been clearly demonstrated that most likely it is the beta diversity of both species groups which regulate equilibrium in the plant community.…”
Section: Beta Diversity Patternssupporting
confidence: 84%
“…Biotic interactions (i.e., competition and facilitation) may become more and more important along the subsequent stages of the invasion continuum [31]. One of the main consequences of the invasion processes could be the disruption and homogenization of the native resident community [92][93][94][95][96], resulting in a loss of species and a reduction in the functional space [42]. Probably, accounting for phylogenetic signal and intraspecific trait variation along with the use of long-term experiments [78] may help to comprehensively understand invasion dynamics, even though not all traits are phylogenetically conserved.…”
Section: Functional Features Of Native Species Pool Facilitating Commmentioning
confidence: 99%
“…In the Mediterranean Basin, well preserved coastal habitats became rarer as the anthropogenic pressure increased, mainly consisting in touristic settlements, habitat fragmentation and inappropriate land management, such as reforestation with alien species [11,[18][19][20][21]. Invasive alien species (IAS) are recognized as an important threat to biodiversity worldwide [22] and especially in rare and extreme environments (such as alpine zone or isolated islands, [23][24][25]). On dune ecosystems, in particular, IAS alter the structure of native communities in different ways: reducing functional, phylogenetic and taxonomic diversities and excluding closely related and ecologically similar taxa [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%